Characterization and biodegradation potential of an aniline-degrading strain of Pseudomonas JA1 at low temperature. Issue 52 (7th November 2016) - Jiang, Yu; Shang, Yu; Zhou, Jun; Yang, Kai; Wang, Hongyu
Abstract: Aniline is a common toxic compound in various industrial processes. It should be removed from effluents before their discharge into water bodies. A cold-tolerant bacterium JA1 capable of utilizing aniline as the sole source of carbon, nitrogen, and energy was isolated from activated sludge samples collected from a sewage treatment plant. The isolate was identified as Pseudomonas species by 16S rDNA sequence analysis. Strain JA1 was able to degrade less than 1600 mg l −1 aniline with high efficiency and grow well at pH varying from 5.0 to 9.0. The suitable temperature ranged from 10 to 35°C. Under optimal conditions (pH 7.0, 25°C), 800 mg l −1 of aniline was almost completely degraded within 24 h. Substrates utilization tests showed that the strain could grow well when sodium acetate, glucose, sodium citrate, benzene, aniline, phenol, nitrobenzene, and m -cresol acted as the sole source of carbon. The adaptation to wide range of aniline concentration, pH, temperature, and different substances made strain JA1 promising for aniline degradation from industrial wastewater.